One Year Outcome and Satisfaction of Presbyopia Correction Using the PresbyMAX® Monocular Ablation Profile - Fu, Dan; Zhao, Jing; Zeng, Li; Zhou, Xingtao (Frontiers in Medicine, 2020)
Purpose: To explore the safety, efficacy, and satisfaction of the PresbyMAX monocular mode for the correction of presbyopia. Methods: Prospective study. Twenty-two patients (mean age 50.6 ± 6.2 years, 11 myopia patients and 11 hyperopia patients) were enrolled. The dominant eye was fully corrected for distance vision; the non-dominant eye was corrected using central PresbyMAX monocular mode. Binocular uncorrected distance visual acuity (BUDVA), near visual acuity (BUNVA), intermediate visual acuity (BUIVA), corrected distance visual acuity (CDVA), and mean spherical equivalent (SE) were tested at 1 day, 1 week, 1 month, 3 months, and 1 year postoperatively. Questionnaire was performed preoperatively, 1 month, 3 months, and 1 year after surgery. Results: At the final visit, the mean safety index was 1.03 ± 0.14. There were 85.7% eyes with the same or better CDVA than the preoperative value, and 17.1% and 2.9% eyes gained 1 line and 2 lines of CDVA, respectively. All treated eyes achieved 20/25 or better BUDVA, and 95.5% achieved 20/32 or better BUNVA, which improved significantly compared with preoperative values (P < 0.001). BUDVA maintained stability from 1 month postoperatively, BUNVA and BUIVA kept stable since 1 week after surgery. Overall satisfaction was 95.5% (21/22) at 3 months visit, and 100% at the last visit. No differences in terms of visual acuity and satisfaction were found between the myopia and hyperopia groups. Conclusion: The PresbyMAX monocular ablation profile was safe and effective in treating presbyopia, with great satisfaction achieved at postoperative 1 year.